Evaluation of Additional Sequential Boost Radiotherapy (RT) After Whole Breast Irradiation (WBI) for Patients with Early Breast Cancer (Ca) - Ferrat Dincoglan; Murat Beyzadeoglu; Omer Sager; Selcuk Demiral; Bora Uysal; Hakan Gamsiz; Onurhan Colak; Fatih Ozcan; Bahar Dirican (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Breast cancer (Ca) comprises the most common cancer in females and constitutes a leading cause of cancer related deaths around the globe. Contemporary treatment protocols established by incorporation of accumulating high level evidence suggest multimodality therapy for patients suffering from breast Ca with combinations of surgery, radiotherapy (RT) and systemic treatment. Surgical options for management of breast cancer typically include breast conserving surgery (BCS) or mastectomy. In current treatment practice, BCS is used as a viable surgical modality for breast Ca management. RT after BCS has been widely adopted for management of the vast majority of patients with breast Ca particularly to achieve improved local control as suggested by collaborative group studies and metaanalyses. Although alternative dose-fractionation schemes may be considered for management of some patients, current widely accepted practice includes the use of conventionally fractionated RT after BCS for breast Ca. Whole breast irradiation (WBI) constitutes a widely recognized breast Ca RT approach which is typically used to deliver a total dose of 45 to 50 Gy over 5 to 6 weeks in daily fractions of 1.8 to 2 Gy. Hypofractionated RT schemes have also been widely accepted as a viable alternative to conventional fractionation with satisfactory treatment outcomes. A typical location for local recurrences of breast Ca includes the primary tumor site within the tumor bed or its vicinity, which justifies the delivery of additional boost dose focused on this area to improve local control rates particularly for patients with high-risk characteristics including younger age, large tumor size, higher grade, extensive intraductal component, close or positive surgical margins. Herein, we assess the utility of delivering an additional sequential boost RT after WBI for patients with early breast Ca in light of the literature.